Depression and Cognition Mediate the Effect of Self-Perceptions of Aging Over Frailty Among Older Adults Living in the Community in China - Yuan, Kun; Luo, Yanyan; Sun, Junjun; Chang, Hongjuan; Hu, Huijie; Zhao, Bingwei (Frontiers in Psychology, 2022)
Objectives The aims of the study were first to investigate the association between self-perceptions of aging and frailty and second to determine whether self-perceptions of aging affects frailty via depressive symptoms and cognitive status among older adults living in the community in China. Methods Among 850 older adults who participated in this cross-sectional study, 822 older adults made valid responses to Tilburg Frailty Indicator, Brief Aging Perceptions Questionnaire, UCLA loneliness scale-8, Mini-Mental State Examination, and Patient Health Questionnaire-9 between March to December 2019. The possible pathways of self-perceptions of aging affecting frailty were analyzed based on the structural equation modeling analysis. Results A total of 21.53% of older adults reported frailty. Correlation analyses showed that higher degrees of frailty were related to greater loneliness, more depressive symptoms, more negative self-perceptions of aging, worse locomotive function, and cognitive status (r = 0.267, r = 0.440, r = 0.481, r = 0.451, r = −0.337; p < 0.001). Multiple regression analysis showed that loneliness, depressive symptoms, self-perceptions of aging, locomotive function, and cognitive status were the five factors to be entered the regression equation, and the variance of joint explanation was 46.60%. SPA had a direct effect on frailty (β = 0.306 and p < 0.001), and SPA indirectly affects frailty by independently affecting depressive symptoms (β = 0.391, 95% CI [0.027, 0.061], and p < 0.001) or cognitive status (β = 0.148, 95% CI [0.009, 0.024], and p < 0.001) of older adults. Conclusion These findings help explain the potential psychological mechanisms through which SPA impacts frailty and may aid community healthcare providers in China in identifying individuals at high risk of frailty. The results suggest that health staff should help older adults improve their perspectives on aging, alleviate or prevent depressive symptoms, and improve cognitive status to delay the progress of frailty and promote healthy aging.